2018
DOI: 10.3390/w10020199
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Leaching from Green Roof Substrates—Can Green Roofs Pollute Urban Water Bodies?

Abstract: Green roofs are an effective stormwater measure due to high water retention capacity and the ability of delaying stormwater runoff. However, low importance is still given to the pollutant leaching potential of substrates used in green roof construction. The aim of the study is to estimate the concentrations and loads of P-PO 4 3− in runoff from extensive and intensive substrates. To achieve this goal, several commonly-used fresh substrates were analyzed for P-PO 4 3− leaching potential in different scale exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
1
15
2
Order By: Relevance
“…Evaluation of the performance of a green roof for nutrient retention versus input rainfall made by Gregoire and Clausen [19] also showed that P concentrations exported from the green roof were greater than those observed in precipitation, however, an analysis of mass export suggested that the green roof actually retained nutrients and metals mass by virtue of its volume retention capacity. An opposite situation has been reported in the previous study [20]. Simulation of the rainfall of 470 mm (reflecting the precipitation from growing season in Poland in 2013), resulted in phosphorus leaching from 0.337 to 2.351 mg/kg of different substrates and was much higher than the load of phosphorus supplied with precipitation.…”
contrasting
confidence: 62%
See 2 more Smart Citations
“…Evaluation of the performance of a green roof for nutrient retention versus input rainfall made by Gregoire and Clausen [19] also showed that P concentrations exported from the green roof were greater than those observed in precipitation, however, an analysis of mass export suggested that the green roof actually retained nutrients and metals mass by virtue of its volume retention capacity. An opposite situation has been reported in the previous study [20]. Simulation of the rainfall of 470 mm (reflecting the precipitation from growing season in Poland in 2013), resulted in phosphorus leaching from 0.337 to 2.351 mg/kg of different substrates and was much higher than the load of phosphorus supplied with precipitation.…”
contrasting
confidence: 62%
“…Simulation of the rainfall of 470 mm (reflecting the precipitation from growing season in Poland in 2013), resulted in phosphorus leaching from 0.337 to 2.351 mg/kg of different substrates and was much higher than the load of phosphorus supplied with precipitation. This study has also shown a high correlation between phosphorus content estimated by HCl extraction and cumulative load in leachate tests, suggesting that the batch of HCl extraction test can be recommended for the comparison and selection of substrates with the focus on potential P leaching [20].…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…The average indicated value was 4.561 ± 0.682 mgP-PO 4 /L. The highest noted values were 3.313 and 6.033 mgP-PO 4 /L which correspond to the extractable P (Table 1) [29]. The results obtained for PRBs showed that tested RMs are efficient in phosphate reduction.…”
Section: Leakages Qualitymentioning
confidence: 81%
“…Initially, P reactive materials (RMs) were successfully used as an additional filter at on-site sewage treatment plants [26,27]. Nowadays, the range of RM applications have been spreading not only to wastewater but also to surface water [28] and green roof leakage treatment [29].…”
Section: Introductionmentioning
confidence: 99%